Nepenthes rafflesiana var. zabawiana (Nepenthaceae), a new variety of pitcher plant from Peninsular Malaysia - Ghazalli, Mohd Norfaizal; A., Latiff; Nikong, D; Anak Besi, E.E.; Mat-Esa, M.I.; Hizamri, Y.; Regina, M.J.; Mohd Masri, S.; Mohd Fahimee, J.; Mohd Shukri, MA. (Malaysian Forester, 2024)
A new variety of pitcher plant, Nepenthes rafflesiana var. zabawiana M.N. Faizal, Latiff et Besi, var. nov., is described from Peninsular Malaysia, specifically from the Setiu Wetlands and Taman Negeri Rompin. This new variety is characterized by its small ear-like appendages below the peristome (0.5-1.3 cm in diameter), which are yellowish-green to reddish-green in colour. Additionally, its upper pitchers are smaller and cylindrical.